ISOLATION AND EVALUATION OF NATURAL GUM EXUDATES OF LANNEA COROMANDELICA (HOUTT.) MERR. AS NATURAL POLYMERIC BINDER AND DRUG RELEASE REGULATING AGENT IN COMPARISON WITH SYNTHETIC AND SEMISYNTHETIC POLYMERS - ANUSHA, V.; UMASHANKAR, M. S. (International Journal of Applied Pharmaceutics, 2025)
Objective: The present research study aims to isolate the natural gum from Lannea coromandelica (Houtt.) Merr and to analyze and explore the polymeric properties specifically binding property and drug release regulating properties of Lannea gum by formulation of tablets using Ibuprofen as model drug. Methods: The natural Lannea gum was compared with standard synthetic and semi-synthetic polymers like Povidone K30 and Hydroxypropyl methyl cellulose K4M (HPMC K4M) respectively as standard polymers with binding property and drug release regulating property. The process includes formulation of total nine batches, where Lannea gum was used at concentrations of 7, 14, 21 mg as a novel binder and drug release regulating agent with above mentioned as binders and drug release regulating agent along with Avicel PH 102 as diluent and disintegrant, Ibuprofen as model drug, magnesium stearate as lubricant and Aerosil as Glidant with the technique of wet granulation method. The compatibility of formulation blend was analyzed by FTIR studies which indicated the gum is compatible with formulation ingredients. The thermal, surface morphological, physical properties of Lannea gum were identified by DSC, SEM and XRD studies respectively. The micromeritic properties of granules like bulk/tapped density, compressibility index, Hausnner’s ratio, angle of repose indicated satisfactory flow properties. Results: The formulated tablets were evaluated for parameters like weight variation, hardness, disintegration time, drug content and In vitro drug release studies. In conclusion it could be confirmed that at 60 min formulation f3 containing Lannea gum produced drug release of 85.27%, f6 containing Povidone K30 produced drug release of 97.47% and f9 comprising HPMC K4M exhibited 81.15% drug release. Conclusion: The study concludes that Lannea gum unveiled superior binding properties than Povidone K30 and slightly low potential with concern to its binding and drug release regulating properties when compared to HPMC K4M. Hence, Lannea coromandelica gum, can be used as a potential polymer in formulation of tablets as a binder and drug release regulating agent.